Impacts of Kampus Mengajar Program on Elementary School Students' Literacy and Numeracy - Ruri Fadhilah Kurniati; Muhammad Assegaf Baalwi; Amelia Panji Sekar Pameling (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This research aims to examine whether or not there is impact of Kampus Mengajar program batch 7 in 2024 on strengthening students’ literacy and numeracy learnings at a total of 37 elementary school in Sidoarjo region. Quantitative data was obtained through tests, that is, the results of pre-test and post-test of literacy and numeracy on class Minimum Competence Assessment, and analysed through normality and hypothesis tests. The normality test of the literacy pre-test shows 24 were normally distributed and 13 not; while the normality test of the literacy post-test confirms 20 were normally distributed and 17 not. The results of the normality test of the numeracy pre-test shows that 32 were normally distributed and 5 not; whereas the normality test of the numeracy post-test demonstrates 26 were normally distributed and 11 not. The hypothesis tests reveal that Kampus Mengajar program batch 7 in 2024 had impacts on strengthening literacy and numeracy learnings in 11 elementary schools, impacted only on the literacy learnings in 2 schools, impacted only on numeracy learnings in 15 schools, and did not do on neither literacy nor numeracy learnings in 9 schools. This research discovers that Kampus Mengajar program batch 7 in 2024 had a less significant impact on strengthening literacy and numeracy learnings among elementary school students in Sidoarjo region since it only affected a small number of the elementary schools. Furthermore, Kampus Mengajar program was more impactful on strengthening numeracy learnings compared to literacy learnings.